2009
DOI: 10.1002/jbm.a.32444
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a prostaglandin EP4 receptor agonist on early fixation of hydroxyapatite/titanium composite‐ and titanium‐coated rough‐surfaced implants in ovariectomized rats

Abstract: The agonist of the prostaglandin EP4 receptor can increase bone density in osteoporosis. Using ovariectomized (OVX) and sham-operated (SO) rats, the effects of the EP4 receptor agonist, ONO-4819, and hydroxyapatite (HA) on implant-bone fixation in implants with a rough surface were investigated. Female Wistar rats (12 weeks old) were divided into either SO or bilateral OVX groups. Twenty four weeks later, either hydroxyapatite/titanium (HA/Ti) composite-coated or Ti-coated implants were implanted into the femo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…146 Hayashi et al demonstrated that titanium-coated rough-surfaced implants had an increased implant fixation strength, if osteoporotic animals were treated with a selective EP4-prostaglandin receptor agonist. 147 Bone Morphogenetic Protein 2 is a clinically approved growth factor for facilitating bone regeneration. Over decades, BMP-2 has shown its osteoinductive properties in various biomaterial scaffolds.…”
Section: Stimulating An Atrophic Environment Around Implants Towards ...mentioning
confidence: 99%
See 1 more Smart Citation
“…146 Hayashi et al demonstrated that titanium-coated rough-surfaced implants had an increased implant fixation strength, if osteoporotic animals were treated with a selective EP4-prostaglandin receptor agonist. 147 Bone Morphogenetic Protein 2 is a clinically approved growth factor for facilitating bone regeneration. Over decades, BMP-2 has shown its osteoinductive properties in various biomaterial scaffolds.…”
Section: Stimulating An Atrophic Environment Around Implants Towards ...mentioning
confidence: 99%
“…In contrast the local release of a selective EP4‐prostaglandin receptor agonist from a mineralized collagen scaffold can increase bone formation 146 . Hayashi et al demonstrated that titanium‐coated rough‐surfaced implants had an increased implant fixation strength, if osteoporotic animals were treated with a selective EP4‐prostaglandin receptor agonist 147 …”
Section: How Can We Modulate the Inflammatory And Foreign Body Respon...mentioning
confidence: 99%